Global Oil Price and Its Economic Impact in Bangladesh - Sultana, Shirin; Uddin, Md. Nasim (Asian Business Review, 2018)
This paper highlighted the plummeting price of oil that is at present the most sensational energy story in the world. This research work outlined the main reasons for the current situation is the low demand for oil as well as concerned companies found it more profitable to extract oil by unconventional methods. In Bangladesh, no changes have been made in the oil price. By figure, at present (June 2017) BPC (Bangladesh Petroleum Corporation) is making profit of Tk 13.77 per liter of Kerosene, of Tk 14.68 per liter of Diesel, of Tk 19.57 per liter of Furnace oil and of Tk 18.75 per liter of jet fuel oil where the very latest world crude oil price come down 35.62. The present study is done to make the overview of the world oil prices and Bangladesh as well using purely secondary data collected mostly from newspaper reports, websites, magazines, journals, periodic, reviews and various published data. This study also investigates the impact of the sharp fall oil price to the economy of Bangladesh. In the study, there is seen negatively correlation with the oil price of the world and that of Bangladesh. This paper will be useful to the all stakeholders even policy makers to take proper initiatives for the adjustment of the plummeting oil price of the world. This present study may disseminate that the BPC, as the government-sponsored firm, cannot make the maximum profit as like the Monopoly Company in Bangladesh, so, the retail consumer may give the benefits of the adjustment with the sharp oil price fall in the world.